Degradation and mechanism analysis of protein macromolecules by functional bacteria in tobacco leaves - Jiang, Chuandong; Kong, Decai; Li, Yangyang; Sun, Jingguo; Chen, Zhenguo; Yang, Mingfeng; Cao, Shoutao; Yu, Cunfeng; Wang, Zengyu; Jiang, Jiazhu; Zhu, Chengguang; Zhang, Nan; et al. (Frontiers in Microbiology, 2024)
Tobacco, a crop of significant economic importance, was greatly influenced in leaf quality by protein content. However, current processing parameters fail to adequately meet the requirements for protein degradation. Microorganisms possess potential advantages for degrading proteins and enhancing the quality of tobacco leaves, and hold substantial potential in the process of curing. To effectively reduce the protein content in tobacco leaves, thereby improving the quality and safety of the tobacco leaves. In this study, tobacco leaf were used as experimental material. From these, the BSP1 strain capable of effectively degrading proteins was isolated and identified as Bacillus subtilis by 16S rDNA analysis. Furthermore, the mechanisms were analyzed by integrating microbiome, transcriptome, and metabolome. Before curing, BSP1 was applied to the surface of tobacco leaves. The results indicated that BSP1 effectively improves the activity of key enzymes and the content of related substances, thereby enhancing protein degradation. Additionally, protein degradation was achieved by regulating the diversity of the microbial community on the surface of the tobacco leaves and the ubiquitin-proteasome pathway. This study provided new strategies for extracting and utilizing functional strains from tobacco leaves, opening new avenues for enhancing the quality of tobacco leaves.